LAYANAN TELE-HEALTH KOMUNIKASI INFORMASI EDUKASI (T-health-KIE) BAGI PASIEN COVID-19 RUANG ISOLASI SEBUAH RUMAH SAKIT SWASTA DI BALI - S. Purnawati; L.P. Indah; I.D.A.I. Primayanti; C.B.J. Lesmana (Buletin Udayana Mengabdi, 2022)
The atmosphere of treatment in the isolation room is scary for Covid-19 patients, especially at the beginning of the pandemic, plus there is "stigma" in the community and the patient must be alone without any family who dares to accompany during hospitalization. All of these conditions make a heavy burden on the patient's psyche. The community service activities are provided mainly using WhatsApp media, as a telehealth service of communication information and education (namely T-health-KIE). The service was conducted from May to September in the year 2021, aimed to provide psychological support and offer correct information about the patient's illness, as well as other relevant information. Patients are also given a package containing snacks and toiletries/body care products as patients’ needs during treatment in the isolation room. The package given is received directly by the patient or the patient's family representative at the hospital. The T-health-KIE has conducted among 59 patients in an isolation room at a private hospital in Bali, consisting of 33 male and 26 female patients, with an age range of 19 to 78 years old. Fortunately, is that there has been a decreased anxiety of patients who threatened in isolation rooms in the 2nd year of the pandemic compared to the previous year (at the beginning of the Covid-19 pandemic). The T-health-KIE service is an innovative and safe health service for health workers during the Covid-19 pandemic. In addition to being useful for patients, it also helps to ease the burden of doctors with a heavy workload in handling Covid-19 patients. Keywords: Covid-19, isolation,telehealth, KIE,communication information education